IbM Kelompok Guru-Guru SD Inpres Sero di Kecamatan Somba Opu Kabupaten Gowa: Menulis Karya Ilmiah - Andi Mulawakkan Firdaus; Nurul Magfirah; Musdalifah Syahrir; Rezki Ramdani (Universitas Muhammadiyah Parepare)
Teachers are currently required to produce scientific work, whereas generally teachers only have no experience in writing scientific papers. The purpose of this program is to increase the knowledge of SD Inpres Sero teachers in Somba Opu District to have competence and independence and to be skilled in making scientific work. The program carried out is training and assistance in writing scientific papers. The method used in this training is the training and mentoring method that is intended for SD Inpres Sero teachers in Somba Opu District. Some of the stages carried out include preparation, observation, action plans, implementation, evaluation and feedback, and assistance in preparing class action research (CAR) and scientific articles. The results of the training show that the training participants have the skills to write scientific articles and produce products that are worthy of being published in scientific journals based on their classroom action research.